Legal Consequences of Sale and Purchase Deeds Made by Unregistered Land Deed (PPAT) Officers at the Land Office - Badriyah, Lailatul (Jurnal Konstatering, 2025)
The transfer of land rights must be proven by an authentic deed made by a PPAT as a guarantee of legal certainty, as stipulated in Article 40 paragraph (1) of PP 24/1997 which requires PPATs to submit sales and purchase deeds along with supporting documents to the Land Office no later than seven working days after signing. However, in practice, PPAT negligence still occurs, so this normative legal research, using a statutory and theoretical approach and using secondary data from primary, secondary, and tertiary legal materials, analyzes the status of PPAT deeds and the legal consequences of delays in registration. The results of the study indicate that PPAT deeds still have strong legitimacy and qualify as authentic deeds with perfect evidentiary power, although the regulatory norms need to be strengthened to be equal to other authentic deeds. Sales and Purchase Deeds are valid as evidence of transfer of rights, but obtain full legal force after registration; so that delays in submitting the deed can reduce legal protection for buyers, although buyers can still take civil suits to obtain an inkracht decision as a basis for registration and legal certainty.